FORMULASI EKSTRAK ETANOL GAMBIR (Uncaria gambir Roxb.) DALAM BEDAK ANTI JERAWAT - Husnul Warnida; Agustiani Masliyana; Sapri Sapri (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Acne occurs due to blockage of pilosebaseus (oil glands) and inflammation causing by Propionibacterium acne, Staphylococcus epidermidis and Staphylococcus aureus. The purpose of the study was to test the antibacterial activity of gambir (Uncaria gambier Roxb.) ethanol extract toward Staphylococcus epidermidis and to formulate gambir ethanol extract into a loose powder dosage form that meets the standards of physical powder quality. Gambir was macerated with 95% ethanol. Activity of gambir ethanol extract against Staphylococcus epidermidis was tested by diffusion method using varying concentrations 3%, 6% and 9% of gambir etanol extract. Afterward, gambir ethanol extract formulated into powder. Analyze of powder physical properties including organoleptic test, homogeneity and particle size distribution. The results showed gambirethanol extract 3%, 6%, 9% has inhibition zone diameter 3.6 mm, 4.2 mm, and 6.8 mm respectively. Gambir ethanol extract powder has a homogeneous, fine size with a light brown color and a distinctive gambir aroma. The average particle size of the powder is 236.17 μm